A atuação do pedagogo no Centro de Referência de Assistência Social em Boa Vista-RR - Silva, Joelma da (2023)
The study focuses on the role of the pedagogue in contexts called non-school spaces. With the intention of reflecting on the possibility of work of the professional graduated in Pedagogy beyond the school wall, which means the expansion of the pedagogue's work field, beyond formal education. The research was centered on the analysis of the pedagogue's performance in the area of Social Assistance. This is a qualitative research, which was used as a data collection instrument through semi-structured interviews, carried out at the Social Assistance Reference Center - CRAS, in the city of Boa Vista-RR, located in the western region, due to its greater territorial coverage. The research participants are pedagogical professionals who work in this space. Data treatment was carried out through content analysis, culminating in the construction of inferences (notation of research results). CRAS is a service that assists people who live in social vulnerability in different ways. The categories of analysis deal with questions of non-formal education, pedagogy, social vulnerability and public services of multifunctional assistance of social assistance. The studies point to the growth of the participation of pedagogues in non-school spaces, being in several areas (health, social assistance, security), and the absence of studies of this nature in the northern region. It appears that the diversified performance of the pedagogue is threatened due to changes in Resolution CNE/CP nº 2, of December 2019, which deals with teacher training aimed at the fragmentation of pedagogue training. The importance of pedagogy to guide social interventions in fields other than formal education was highlighted. The research results show a weakness in the initial training of professionals who work in the multidisciplinary team (pedagogue, social worker, psychologist) at CRAS, based on the different curricular matrices analyzed. It was identified that the members of the multidisciplinary team do not carry out specific work in their area, but rather fulfill the same demands as the institution. This makes the contribution of each professional difficult and vulnerable, especially the pedagogue who is the object of this study. The pedagogue mentioned that she did not participate in any training to take on the position, thus developing her professional skills based on the perception of the team's practices. Another point is the salary remuneration of the pedagogue who works at CRAS, which is lower than the others members of the multidisciplinary team. It was also noted that the professional participating in the research develops her work through the skills she acquired in practice, given the lack of professional training in the actual exercise of her role. In this sense, the study presents, in general, the need for pedagogues in these spaces and the contribution they can bring to addressing the vulnerabilities presented. The possibility of discussion and reflection on the subject is relevant with the focus on this area of activity of the pedagogue, aiming to present such aspects to society, in addition to contributing to other researchers in other areas of knowledge. In this way, the study has technical, political, social and scientific feasibility. This is an impact study, as it makes it possible to verify something that has not yet been adequately highlighted in the context of Roraima.